2015
DOI: 10.1038/nature14157
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian polymerase θ promotes alternative NHEJ and suppresses recombination

Abstract: The alternative nonhomologous end-joining (alt-NHEJ) machinery facilitates a number of genomic rearrangements, some of which can lead to cellular transformation. This error-prone repair pathway is triggered upon telomere de-protection to promote the formation of deleterious chromosome end-to-end fusions1,2,3. Using next-generation sequencing technology, we found that repair by alt-NHEJ yields non-TTAGGG nucleotide insertions at fusion breakpoints of dysfunctional telomeres. Investigating the enzymatic activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

44
672
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 616 publications
(749 citation statements)
references
References 36 publications
44
672
5
Order By: Relevance
“…The reduction in proofreading capacity of lagging-strand polymerases (Reijns et al 2015), coupled with increased fork stalling at telomeric locations (Lormand et al 2013) could result in an incompletely replicated template (Chow et al 2012) that is ligated with the leading strand fulllength chromatid to create a nonpalindromic fusion (Stohr et al 2010). The higher incidence of templated insertions we detected at intra-chromosomal junctions also suggests an active contribution of DNA synthesis to repair (Lowden et al 2011), conceivably involving the A-NHEJ-associated DNA polymerase theta (Yousefzadeh et al 2014;Ceccaldi et al 2015;Mateos-Gomez et al 2015) or alpha (Reijns et al 2015) by way of incomplete primer removal. Thus, the more prominent role of LIG1 in intra-chromosomal fusion events provides a mechanistic link to the asymmetric architecture via distinctive chromatid replication.…”
Section: A-and C-nhej Of Dysfunctional Human Telomeresmentioning
confidence: 66%
“…The reduction in proofreading capacity of lagging-strand polymerases (Reijns et al 2015), coupled with increased fork stalling at telomeric locations (Lormand et al 2013) could result in an incompletely replicated template (Chow et al 2012) that is ligated with the leading strand fulllength chromatid to create a nonpalindromic fusion (Stohr et al 2010). The higher incidence of templated insertions we detected at intra-chromosomal junctions also suggests an active contribution of DNA synthesis to repair (Lowden et al 2011), conceivably involving the A-NHEJ-associated DNA polymerase theta (Yousefzadeh et al 2014;Ceccaldi et al 2015;Mateos-Gomez et al 2015) or alpha (Reijns et al 2015) by way of incomplete primer removal. Thus, the more prominent role of LIG1 in intra-chromosomal fusion events provides a mechanistic link to the asymmetric architecture via distinctive chromatid replication.…”
Section: A-and C-nhej Of Dysfunctional Human Telomeresmentioning
confidence: 66%
“…Polθ has multiple documented activities in DNA replication and repair, including alt-EJ, replication repair, translesion synthesis, and replication initiation (4)(5)(6)(7)(8)10,15,31,32). Although the activities and cellular functions of Polθ-polymerase have been investigated, little is understood regarding the enzymatic activities of Polθ-helicase.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the biochemical activities and cellular functions of Polθ have become a priority because it has been found to be essential for the error-prone doublestrand break (DSB) repair pathway known as microhomology-mediated end-joining (MMEJ) or alternative end-joining (alt-EJ) (3)(4)(5)(6)(7)(8)(9). Remarkably, Polθ expression has also been shown to be important for the proliferation of cells deficient in the homologous recombination (HR) pathway, such as due to mutations in BRCA1 or BRCA2 (4,10). Recent studies additionally demonstrate that Polθ is responsible for random DNA integration into the genomes of mammalian cells, and for T-DNA integration into plant genomes (11)(12)(13).…”
mentioning
confidence: 99%
“…Homologous recombination-deficient tumors depend on other error-prone mechanisms for double-stranded break repair, such as the Polθ/PARP1-mediated alternative end-joining pathway. 10,11 The reliance on alternative end-joining repair pathways subsequently renders homologous recombination-deficient tumors more sensitive to chemotherapy as well as to PARPi. 3,4,[12][13][14][15][16][17][18][19] Only one PARPi has been FDA approved for the treatment of ovarian cancer, olaparib, and this is only in the setting of BRCA mutation and at least three prior lines of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…6 The BRCA1/2 genes have an important role in homologous recombination, and other genes involved in homologous recombination, such as BRIP1, RAD51C, and RAD51D, have also been implicated as less common sources of genetic susceptibility to high-grade serous carcinoma. [6][7][8][9] Homologous recombination-deficient high-grade serous carcinomas (including BRCA1/2 mutations) depend on alternative, error-prone mechanisms for doublestrand break repair, such as the Polθ/PARP1-mediated alternative end-joining pathway for DNA repair, 10,11 and subsequently have been shown to have increased sensitivity to platinum chemotherapy and to poly ADP-ribose polymerase inhibitors (PARPi), and improved overall survival. 3,4,[12][13][14][15][16][17][18][19] Studies from The Cancer Genome Atlas Research Network (TCGA) demonstrated that nearly one-third of ovarian high-grade serous carcinomas had BRCA1-/2 alterations, which included 20% with either germline or somatic mutations in BRCA1/2 and an additional 11% with BRCA1 epigenetic silencing via hypermethylation.…”
mentioning
confidence: 99%